The Influence of Factors; Human Resource Management, Production, and Marketing on the Financial Performance of Small-Sized Enterprises in Jayapura City - Mugiati, Mugiati (Information Management and Business Review, 2015)
This study aims to identify and analyze the influence of human resource management, production and marketing, on the financial performance of Small-sized enterprise in Jayapura City. Data collection methods used were observation, interviews, and questionnaires. Data were analyzed by applying SEM (structural equation modeling analysis method by making use of Amos Software. The results showed that the factors of human resource management and marketing not affect the financial performance of small-sized enterprise in Jayapura. Then the production factor affect the financial performance of small-sized enterprise in Jayapura.